PENGENDALIAN PENYAKIT TUNGRO MELALUI ELIMINASI PERAN VEKTOR WERENG HIJAU DENGAN PENGENDALIAN RAMAH LINGKUNGAN - Dini Yuliani; I Nyoman Widiarta (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2017)
Green leafhopper (GLH)plays an important role in tungro disease epidemics. Reduce the activity of GLHsuckasvectorsof tungro virus was effective to limit transmission of the virus. Integrated control of tungro disease may involve multiple components at once including using sambilata with entomopathogenicfungus Metarhiziumanisopliae. This research was conducted to determine the effect of sambilata and M.anisopliaein controlling the GLH as tungro virus vectors. The experiment was conducted in tungro endemic areas in Tanjungsiang,Subang District at dry season 2013 and wet season 2013/2014. Experiments using split plot design with four replications. The main plot was consists of GLH resistant varieties(IR66), tungro resistant varieties (Inpari 9), and check varieties(Ciherang). The subplots were M.anisopliae applications, sambilata, and control. Application was done on rice plant age 14, 28 and 42 days after planting (DAP).The results showed that the intensity of tungro on Ciherang showed the highest intensity compared toIR66 and Inpari9. Effect of entomopathogenic fungus M.anisopliae application to tungro disease showed a lower intensity compared with sambilata extracts and control. The intensity of tungro disease in farmers’ fields as a comparison of experiment was high enough on average between 1 until 69%. In general, the density of GLH population began to increase on the observation of 14 to 28 DAP. GLH population density was highest at 28 DAP. However, the population density of GLH decreased at 42 until 56 DAP.